Kaitan Ruang Terbuka Hijau dengan Kenyamanan Termal Perkotaan - Sobri Effendy; Ferdy Aprihatmoko (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2014)
The existence of green open space in urban areas is very important in influencing the conditions of thermal comfort. The objective of this research was to analyze the relationship between green open space and human comfort for the city of Yogyakarta. We employed Temperature Humidity Index (THI) with input air temperature and relative humidity. The THI value was obtained from four green open space categories those are point, line, area and non-green space. The results showed that the green open space has a positive effect on lowering the air temperature through the cooling effect and providing more comfortable conditions than the place with non-green open space. Based on this research, the city of Yogyakarta could be categorized as quite comfortable.